Coherence of the Metaphor of God's Armor in Ephesians 6:10-20 and Its Implications for the Theological Construction of Spiritual Warfare - Selvester Melanton Tacoy (Jurnal Jaffray, 2023)
Paul in Ephesians 6:10-20 uses the metaphor of God's armour to explain the spiritual warfare believers face. Of course, the metaphors that Paul put forward are full of meaning based on the context of life at that time in which the life of the people in Ephesus and Asia Minor, in general, had a relationship with the worship of the gods. Using the grammatical-historical method, the writer found that the metaphor of the armour of God that Paul put forward in Ephesians 6:10-20 also has coherence (connectedness, unity) of meanings, ideas, and ideas between these metaphors. This coherence will contribute to efforts to build the theological construction of spiritual warfare and the life practices of believers to face spiritual warfare.